The evaluation on service quality courses offered by Institute of Management Melaka (IMM) / Roslinawati Ibrahim - Ibrahim, Roslinawati (2005)
The purpose of study is to identify how consumers or participants evaluate the service quality provided by Institute of Management Melaka (IMM) and whether they are satisfied or dissatisfied with the services provided by company. Quality in services is not engineered at the manufacturing plant, the delivered intact to the customer. Most services cannot be counted, measured, inventoried, tested, and verified in advance of sale to ensure quality delivery. Furthermore, the performance of services-especially those with the high labor content-often differs among employees, among customers, and from day to day. For this reason, service qualities highly dependent on the performance of employees, an organizational resource that cannot be controlled to the degree that components of tangible goods can be engineered. Therefore, if a company serious about determining the quality of their service, they should at least study a representative sample of their customer base. This paper consists of five chapters which explain the subject matter in stages. Chapter 1 explains the introduction and background of the study. Chapter 2 explains the literature review, which relates to the subject studied and theoretical framework which act as a guide to the research flow and process. For chapter 3, research methodology is explained, which consist of methods and sampling techniques be used. Data findings and discussions is explained in chapter 4, derived from the information obtain from respondents. And finally, chapter 5 contain summary of results and findings, which explain conclusions and recommendations.